Hubungan Kelembagaan dan Relasi Antaraktor dalam Pengawasan Partisipatif pada Pilkada Kabupaten Mojokerto Tahun 2024 - Suprapto; Mustopa, Deni; Roifany, Rizky Amalia; Perdana, Varyzto Arya (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2025)
Participatory oversight in elections is an important instrument to maintain the integrity of electoral democracy, where Bawaslu, in particular, plays a role in activating public involvement through various communication strategies. However, the effectiveness of public relations practices at the local level, such as in Mojokerto district, still faces structural and cultural challenges, so it needs to be examined as a social practice influenced by the local context and actor dynamics. This study examines institutional relationships and inter-actor dynamics in public relations practices at the Mojokerto District Election Supervisory Agency (Bawaslu) in the context of participatory election monitoring. Using a qualitative approach and a single case study design, data collection was conducted through observation, interviews, and document analysis with informants from Gakkumdu, ad hoc supervisors, and local officials who were then validated through triangulation and member checking, and analyzed using a thematic approach. The findings show that the Mojokerto District Bawaslu's public relations practices are influenced by the institutional structure, the capacity of local actors, and the socio-cultural context of the community. Social media is used not only to disseminate information, but also to build an image and mobilize public participation, although its effectiveness is still constrained by limited human resources, the digital divide, and weak institutional coordination. Using structuration and practice theory, this study confirms that PR communication strategies are adaptive and relational, reflecting local actors' negotiations in responding to digital habitus and democratic dynamics at the grassroots level.